2020
DOI: 10.3390/ijerph17186543
|View full text |Cite
|
Sign up to set email alerts
|

Do Targeted User Fee Exemptions Reach the Ultra-Poor and Increase their Healthcare Utilisation? A Panel Study from Burkina Faso

Abstract: Background: A component of the performance-based financing intervention implemented in Burkina Faso was to provide free access to healthcare via the distribution of user fee exemption cards to previously identified ultra-poor. This study examines the factors that led to the receipt of user fee exemption cards, and the effect of card possession on the utilisation of healthcare services. Methods: A panel data set of 1652 randomly selected ultra-poor individuals was used. Logistic regression was applied on the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Educational level was a categorical variable with 16 categories (1 none; 2 nursery school; 3 CP1 4 CP2; 5 CE1 6 CE2; 7 CM1; 8 CM2; 9 Sixième; 10 Cinquième; 11 Quatrième; 12 Troisième 13 Seconde; 14 Première; 15 Terminale; 16 Supérieur). We dichotomised the variable (no education and education) as done by previous studies [ 32 , 33 ]. We did so because the educational level of the ultra-poor people is generally very low.…”
Section: Methodsmentioning
confidence: 99%
“…Educational level was a categorical variable with 16 categories (1 none; 2 nursery school; 3 CP1 4 CP2; 5 CE1 6 CE2; 7 CM1; 8 CM2; 9 Sixième; 10 Cinquième; 11 Quatrième; 12 Troisième 13 Seconde; 14 Première; 15 Terminale; 16 Supérieur). We dichotomised the variable (no education and education) as done by previous studies [ 32 , 33 ]. We did so because the educational level of the ultra-poor people is generally very low.…”
Section: Methodsmentioning
confidence: 99%
“…While there have been long-standing pleas to take into account the indigents (2), and policies for universal health coverage are supposed to be designed with the idea of ‘leaving no one behind’, little has actually been done to address their specific needs. The user fee exemption alone, as well as programs linking performance-based financing and equity measures, have shown their inadequacy in increasing the use of health services for the indigents (5,6,18). There is a need to design and test interventions that are better adapted to their situation and that include support throughout their care pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that these payment exemptions have not significantly increased the use of health services by the selected indigents (5,6). These indigents, who are mainly unmarried adults and older adults (particularly widow(er)s and older women) (7), may face a multitude of other barriers such as psychological stress (8), social exclusion (9), or limitations in physical functioning (7) that prevent them from accessing health services.…”
Section: Introductionmentioning
confidence: 99%
“…Benefit design of health insurance and other social protection schemes has been shown to influence patient and provider behaviors, affecting health services utilization and provision [21][22][23][24][25]. Studies on the impact of user fee exemptions for health services on health care utilization have shown mixed results depending on target population and types of services [26][27][28][29]. In the case of diabetes care, in theory, if cost remains a barrier to accessing particular services, such as fasting plasma glucose (FPG) tests and medications, reducing these barriers may encourage their utilization.…”
Section: Role For Public Social Protection Schemes In Diabetes Care and Managementmentioning
confidence: 99%